Realitas Desain Lembar Kerja Siswa pada Bahan Bilangan Bulat Menggunakan Konteks Pariwisata Musi Rawas - Sukasno, Sukasno; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Somakim, Somakim (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This study aims to design student worksheets on integer material using the context of Musi Rawas tourism. The designed worksheets are expected to provide students with a more engaging and relevant learning experience by incorporating real-life examples and problems related to the local tourism industry. This study uses a design research method with validation studies, including preliminary design and the design experiment (pilot experiment). The results of this study show that the designed worksheets effectively integrate integer concepts with the context of Musi Rawas tourism, making the learning experience more meaningful and enjoyable for students. The study concludes that contextualised learning materials, such as these worksheets, can significantly enhance students' understanding and retention of mathematical concepts.